Analysis Of Netizens' Language Impolence In The Comments Column On The Instagram Account @Lambe - Amri, Yusni Khairul; Azzahra, Destyanti (BIRCU, 2024)
Social networks are part of communication media. Instagram is a social network that has many users, its users range from children to the elderly. Social networks centered on photo and video platforms are currently experiencing extraordinary popularity, but it cannot be denied that different impacts can occur due to each person's reaction. As a social networking user, various impacts can arise, such as impolite language and violating the rules of politeness. The results of this analysis show that there is language impoliteness of internet users in the comments column of the @lambe_turah Instagram account regarding the news